(untitled) (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2026)
This article advocates for practice-oriented pedagogy in language teacher education, illustrating a method where students lead lessons and provide peer feedback. This approach bridges theory and practice, developing essential skills and self-efficacy in future educators.